Continental‐extent patterns in amphibian malformations linked to parasites, chemical contaminants, and their interactions. (19th October 2017) - Haas, Sarah E.; Reeves, Mari K.; Pinkney, Alfred E.; Johnson, Pieter T. J.
Abstract: Widespread observations of malformed amphibians across North America have generated both concern and controversy. Debates over the causes of such malformations—which can affect >50% of animals in a population—have continued, likely due to involvement of multiple causal factors. Here, we used a 13‐year dataset encompassing 53, 880 frogs and toads from 422 wetlands and 42 states in the conterminous USA to test hypotheses relating abnormalities and four categories of potential drivers: (i) chemical contaminants, (ii) land use practices, (iii) parasite infection, and (iv) targeted interactions between parasites and pesticides. Using a hierarchically nested, competing‐model approach, we further examined how these associations varied spatially among geographic regions. Although malformations were rare overall (average = 1.6%), we identified 96 hotspot sites with 5%–25% abnormal individuals. Using the full dataset of 934 collections (without data on parasite infection), malformation frequency was best predicted by the presence of oil and gas wells within the watershed. Among collections also examined for parasite infection ( n = 154), average parasite load and its interaction with pesticide application positively predicted malformations: wetlands with a greater abundance of the trematode Ribeiroia ondatrae were more likely to have malformed amphibians, but these effects were strongest when pesticide application was also high, consistent with prior experimental research. Importantly, however, the influence of these factors also varied regionally, helping explain divergent results from previous studies at local scales; parasite infection was more influential in the West and Northeast, whereas pesticide application and oil/gas wells correlated with abnormalities in the Northeast, Southeast, and western regions of the USA. These results, based on the largest systematic sampling of amphibian malformations, suggest that increased observations of abnormal amphibians are associated with both parasite infection and chemical contaminants, but that their relative importance and interaction strength varied with the spatial extent of the analysis. Abstract : Our paper investigates how multiple forms of environmental change—including pesticide application, land use practices, petroleum wells, parasitic infection, and synergistic effects—influence the biological phenomenon of amphibian malformations, which has attracted broad research attention both across North America and globally.